2015
DOI: 10.1093/femsle/fnv104
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenotrophic culture enrichment reveals rumenLachnospiraceaeandRuminococcaceaeacetogens and hydrogen-responsiveBacteroidetesfrom pasture-fed cattle

Abstract: Molecular information suggests that there is a broad diversity of acetogens in the rumen, distinct from any currently isolated acetogens. We combined molecular analysis with enrichment culture techniques to investigate this diversity further. Methane-inhibited, hydrogenotrophic enrichment cultures produced acetate as the dominant end product. Acetyl-CoA synthase gene analysis revealed putative acetogens in the cultures affiliated with the Lachnospiraceae and Ruminococcaceae as has been found in other rumen stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 24 publications
5
41
0
Order By: Relevance
“…Multivariate regression analysis indicated that the association between plasma acetate and SAT PRDM16 mRNA remained significant after controlling for age, sex, BMI, insulin sensitivity ( M value) and diabetes, hypertension, or dyslipemia therapy, but not after controlling for family Ruminococcaceae RA, suggesting this bacterial family as the most important source of plasma acetate. In agreement with this suggestion, one recent study found acetate biosynthesis to be correlated with Firmicutes RA, being those bacteria from Ruminococcaceae family (which was the most abundant) considered as important acetate‐producing bacteria in rumen studies …”
Section: Discussionsupporting
confidence: 56%
“…Multivariate regression analysis indicated that the association between plasma acetate and SAT PRDM16 mRNA remained significant after controlling for age, sex, BMI, insulin sensitivity ( M value) and diabetes, hypertension, or dyslipemia therapy, but not after controlling for family Ruminococcaceae RA, suggesting this bacterial family as the most important source of plasma acetate. In agreement with this suggestion, one recent study found acetate biosynthesis to be correlated with Firmicutes RA, being those bacteria from Ruminococcaceae family (which was the most abundant) considered as important acetate‐producing bacteria in rumen studies …”
Section: Discussionsupporting
confidence: 56%
“…3B) were dominant in dairy cows' rectal contents. Ruminococcaceae could break down cellulose and disaccharide to formic acid and acetic acid (Gagen et al, 2015). The diet of dairy cows is rich in cellulose and carbohydrates which are digested by ruminal microbes.…”
Section: Microbial Composition In the Hindgut Region Of Healthy Dairymentioning
confidence: 99%
“…In ZDT kelp enrichments, four different Firmicutes taxa were enriched; Clostridium , Anaerosporobacter , Lachnospiraceae -Incertae_Sedis, and Paenibacillus . Anaerosporobacter, a strictly anaerobic spore former, and other Lachnospiraceae members were previously isolated from cellulose and xylan-pectin enrichments of cow feces (Ziemer, 2014), and are frequently encountered within the human gut microbiota (Gagen et al, 2015; Lau et al, 2016; Martinez et al, 2013; Nava, Friedrichsen & Stappenbeck, 2011). Members of the genus Paenibacillus are globally distributed facultative anaerobes (Li et al, 2014), some of which are known to exhibit superior plant biomass degradation capacities (Eida et al, 2012).…”
Section: Resultsmentioning
confidence: 99%